Community Service Program to Increase the Effectiveness and Efficiency of Organic Fertilizer from Goat Faeces in Wonorejo Village, Baluran National Park Buffer Zone - Azizah, Siti; Djunaidi, Irfan H.; Achadiah, Rachmawati; Siti, Hamidah; Ema, Titisari Yunita (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The Community Service Program was carried out in Wonorejo Village, Banyuputih District, Situbondo. The program implementer is a Community Service team and students participating in MMD 1000 Villages in 2023 funded by MMD 1000 Villages Grant Universitas Brawijaya. The target recipients of the program are members of the Soponyono Kendal farmers group that produces organic fertilizer and the purpose of the program was to aid facilities and training for effective organic fertilizers processing acivities. The methods used are Focus Group Discussion, hybrid extension, providing modules, providing production advice, and assistance in making NIB/BIN (Business Identification Number) as legalization of business production. The result is that the program has succeeded in achieving the planned output target. Moreover, this activity is also able to involve the village government and BABINSA (Bintara Pembina Desa/Village Development Officer).